Customer Service Video Series - Havens, Jeff (Pearson, 2015)
The fast, fun, and complete video guide to delivering outstanding customer service! Description In an era where many companies offer similar products and services at similar prices, it's hard to stand out. But if you offer the best customer service around, you'll win loyal customers who keep coming back, and tell their friends to do the same. If that sounds great to you, this complete video course is exactly what you need. Jeff Havens's Customer Service brings together all the knowledge anyone needs to deliver outstanding customer service, and help others do it, too! One of North America's leading presenters on business success, Havens brings fun to the learning process, so his audiences enjoy every minute#x97;and never forget his crucial takeaways. Now, in 25 minutes of powerfully compelling video, Havens covers everything customer service professionals and managers need to know: how to create a physical or online environment that attracts and engages the best customers ... how to practice the personal qualities that lead to successful customer interactions ... how to use active listening and eye contact to connect with customers ... how to recognize and avoid ineffective customer service techniques ... how to uncover small details and improvements that can make customers happy ... how to deal with irate customers ... why processes are important, and when to consider out-of-the-box approaches to helping a customer. There's never been a quicker way to improve your customer service: just watch! About the Instructor A former teacher and stand-up comedian, Jeff Havens has become one of North America's most popular business presenters. His extraordinary ability to deliver high-quality education in an entertaining way has earned him dozens of repeat clients, all of whom appreciate his insistence that education is the only way that we improve at anything, and that we'll all improve better and faster if we enjoy the learning process. By combining traditional presentation content with the entertainment value of a comedy show, Havens has found enthusiastic audiences in government, academia, small businesses, and the Fortune® 50, all while still being one of the youngest members of the professional speaking circuit. A Phi Beta Kappa graduate of Vanderbilt University, he lives in Michigan with his wife, Laura, and their dog, Pancake. He is author of Us vs. Them: Redefining the Multi-Generational Workplace to Inspire Your Employees to Love Your Company, Drive Innovation, and ...